Novel p-n heterojunction BiOI/CeO2 photocatalyst for wider spectrum visible-light photocatalytic degradation of refractory pollutants - Wen, Xiao-Ju; Niu, Cheng-Gang; Zhang, Lei; Zeng, Guang-Ming (Dalton transactions : an international journal of inorganic chemistry, 2017)
Recently, visible-light-driven photocatalysts have been widely used in environmental pollutant remediation. In the present study, BiOI/CeO 2 p-n junction photocatalysts were successfully fabricated using a facile in situ chemical bath method. The BiOI/CeO 2 p-n junction photocatalysts exhibited excellent photoactivity for the decomposition of the refractory pollutant bisphenol A (BPA) and methylene orange (MO) under visible light illumination. The sample with a 1 : 1 mole ratio of BiOI : CeO 2 possessed the highest photocatalytic performance out of all of the as-obtained catalysts. Mott-Schottky plots indicated that p-n junctions were successfully constructed between BiOI and CeO 2 . The optical and electrical properties of the materials demonstrate that the introduction of BiOI can broaden the visible-light absorption region of CeO 2 , and the transfer rate of the electron-hole pairs dramatically improves through forming a p-n junction. Furthermore, the BPA degradation efficiency exhibited excellent photostability after four consecutive cycles. These features show that the BiOI/CeO 2 p-n junction has great application potential for refractory pollutant removal from wastewater. A novel BiOI/CeO 2 photocatalyst with high photocatalytic performance was successfully synthesized via a facile in situ precipitation method. The enhanced photocatalytic performance is ascribed to the formation of a p-n junction, which promotes carrier separation.